Consumption of Whey in Combination with Dairy Medium‐Chain Fatty Acids (MCFAs) may Reduce Lipid Storage due to Urinary Loss of Tricarboxylic Acid Cycle Intermediates and Increased Rates of MCFAs Oxidation. Issue 12 (3rd November 2017) - Amer, Bashar; Clausen, Morten Rahr; Bertram, Hanne Christine; Bohl, Mette; Nebel, Caroline; Zheng, Hong; Skov, Thomas; Larsen, Mette Krogh; Gregersen, Søren; Hermansen, Kjeld; Dalsgaard, Trine Kastrup
Abstract : Scope: The aim of the paper is to investigate whether changes in the metabolome could explain observed changes in body composition in overweight adults after consumption of butter with high level of medium‐chain fatty acids (MCFAs) in combination with casein or whey. Methods and results: With GC‐TOF and LC‐Q/MS, metabolites in plasma and urine from a 12‐week randomized double‐blinded human intervention including 52‐abdominally overweight adults were analyzed. The participants consumed 63 g per day of milk fat (high or low in MCFAs) and 60 g per day of protein (whey or casein). Urinary loss of the tricarboxylic acid cycle metabolites and a concomitantly increase of glycerol in blood were observed in the whey + high‐MCFAs group, indicating potential lower anabolic processes, such as lipogenesis, by draining substrates. High intake of MCFAs resulted in elevated level of urinary adipic (independently of protein type) and plasma sebacic acid (with whey), indicating a potential increase in oxidation of MCFAs, which might lead to energy loss. Conclusion: The type of protein showed highest effect on the overall metabolic profiles, but ω‐oxidation of MCFAs in the liver seemed to be the main reason for the observed reduction in body fat mass after consumption of high MCFAs, independent of type of protein. Abstract : When feeding overweight people with high and low level of medium chain fat and two different milk proteins, casein and whey, the type of protein shows the highest effect on the overall metabolic profiles. However, the level of medium chain fat and its metbolic degradation seem to be responsible for the observed loss in body fat.